Use of technology and Scrum as an agile methodology to favor the development of balanced teamwork enrichment skills in higher education subjects - Turcios-Esquivel, Ana Monica; Aviles-Rabanales, Erendira Gabriela; Sayeg-Sanchez, Gibran (IEEE Global Engineering Education Conference, 2023)
This paper shows a proposal to enhance balanced teamwork through the enrichment of the teaching-learning process with the use of technology, and with the application of agile methodologies, such as Scrum. The focus is that students work in a simulated situation using the Scrum methodology, allowing them to develop communication skills, leadership, mutual support, among others, as well as obtain timely feedback on their performance.